2020
DOI: 10.1136/medethics-2020-106494
|View full text |Cite
|
Sign up to set email alerts
|

The carnage of substandard research during the COVID-19 pandemic: a call for quality

Abstract: Worldwide there are currently over 1200 research studies being performed on the topic of COVID-19. Many of these involve children and adults over age 65 years. There are also numerous studies testing investigational vaccines on healthy volunteers. No research team is exempt from the pressures and speed at which COVID-19 research is occurring. And this can increase the risk of honest error as well as misconduct. To date, 33 papers have been identified as unsuitable for public use and either retracted, withdrawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 34 publications
1
115
0
8
Order By: Relevance
“…7 Other researchers have attempted to show that COVID-19 ICU patients had a decreased trend of mortality if they had also received "Chinese herb therapy" during the course of their disease [20]. 8 Research ethics committees and journal peer reviewers need to ensure robust analysis in the setting of a flurry of COVID-19 submissions [21]. In the marketplace, aligning with FDA regulations, the American Herbal Products Association, the Consumer Healthcare Products Association, the Council for Responsible Nutrition, and the United Natural Products Alliance, have advised sellers of dietary supplements (e.g., vitamins, minerals, herbs) that these products must not claim to prevent, treat, or cure COVID-19 [22].…”
Section: Discussionmentioning
confidence: 99%
“…7 Other researchers have attempted to show that COVID-19 ICU patients had a decreased trend of mortality if they had also received "Chinese herb therapy" during the course of their disease [20]. 8 Research ethics committees and journal peer reviewers need to ensure robust analysis in the setting of a flurry of COVID-19 submissions [21]. In the marketplace, aligning with FDA regulations, the American Herbal Products Association, the Consumer Healthcare Products Association, the Council for Responsible Nutrition, and the United Natural Products Alliance, have advised sellers of dietary supplements (e.g., vitamins, minerals, herbs) that these products must not claim to prevent, treat, or cure COVID-19 [22].…”
Section: Discussionmentioning
confidence: 99%
“… 64 , 65 The rush to publication has now been documented in peer-reviewed journals, with articles being published at extraordinary speeds in the early phases of the pandemic 65 , and several notable instances of articles being later retracted, withdrawn, or having an expression of concern issued. 66 The situation is unlikely to change in the near future, as a review of ClinicalTrials.gov has identified a concerningly large proportion of studies with an expected low level of evidence. 67 Accordingly, a recent systematic review which examined 42 guidelines related to COVID-19 released in the spring/summer of 2020 found that the quality of all was poor, especially with respect to the rigour of their development.…”
Section: The Infodemicmentioning
confidence: 99%
“…An example of the last is the little consideration given to the known cardiotoxicity of the combination of hydroxychloroquine and azithromycin early on in the pandemic. Issues surrounding patients’ participation in clinical studies have also been observed: in her analysis of COVID-19 papers unsuitable for publication, Bramstedt identified issues surrounding informed consent as the second most common source of concerns [35]. In addition to the ethical problems this poses, it could also weaken the trust that patients and the broader community afford researchers, with detrimental consequences for public health in the long term.…”
Section: Stage 1: Data Collection and Interpretationmentioning
confidence: 99%